Protonation and deprotonation induced organo/hydrogelation: Bile acid derived gelators containing a basic side chain - Maitra, Uday; Chakrabarty, Arkajyoti (Beilstein Journal of Organic Chemistry, 2011)
Two bile acid derived molecules containing basic amino groups are reported to be efficient and unusual gelators of organic and aqueous solvents.
Keywords: bile acid derived amines; organogelator and hydrogelator; protonation and deprotonation induced gelation; SEM and POM; thermal stability